The xylem as battleground for plant hosts and vascular wilt pathogens - Yadeta, Koste; Thomma, Bart (Frontiers in Plant Science, 2013)
Vascular wilts are among the most destructive plant diseases that occur in annual crops as well as in woody perennials. These diseases are generally caused by soil-borne bacteria, fungi and oomycetes that infect through the roots and enter the water-conducting xylem vessels where they proliferate and obstruct the transportation of water and minerals. As a consequence, leaves wilt and die, which may lead to impairment of the whole plant and eventually to death of the plant. Cultural, chemical and biological measures to control this group of plant pathogens are generally ineffective, and the most effective control strategy is the use of genetic resistance. Owing to the fact that vascular wilt pathogens live deep in the interior of their host plants, studies into the biology of vascular pathogens are complicated. However, to design novel strategies to combat vascular wilt diseases, understanding the (molecular) biology of vascular pathogens and the molecular mechanisms underlying plant defense against these pathogens is crucial. In this review we discuss the current knowledge on interactions of vascular wilt pathogens with their host plants, with emphasis on host defense responses against this group of pathogens.